The distribution of allele frequencies of the 15 Short Tandem Repeats loci in Elazığ population, Turkiye - Aziz Aksoy; Mehmet Tokdemi̇r; Vahit Konar (Medicine Science)
The DNA within the Human Genome involves loci with high polymorphism such as short tandem repeats (STR). The STR polymorphism analysis is extensively used for numerous purposes such as identification studies in forensic sciences, paternity tests, genome mapping, and population studies. In this study, blood and swab samples were obtained from 200 unrelated healthy individuals living in Elazig province. DNA was amplified via the AmpFlSTR Identifiler PCR Amplification Kit (Applied Biosystems, USA) to analyze the 15 STR loci. Using the ABI PRISM310 Genetic Analyzer capillary electrophoresis, the samples were analyzed and the allelic ladder was used to compare and identify the alleles of the samples, the distribution of the allele frequencies and peak values were examined. For statistical analysis Arlequin v.3.11 and PowerStats v.1.2 were used to assess the data. To determine if the allele frequencies were compatible with the Hardy-Weinberg (HW) equilibrium, the Markov chain and the Fisher's exact test p-value (p [Med-Science 2024; 13(4.000): 763-8]